2017
DOI: 10.1111/acer.13431
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions, Memory, and Social Cognitive Deficits and Recovery in Chronic Alcoholism: A Critical Review to Inform Future Research

Abstract: Alcoholism is a complex and dynamic disease, punctuated by periods of abstinence and relapse, and influenced by a multitude of vulnerability factors. Chronic excessive alcohol consumption is associated with cognitive deficits, ranging from mild to severe, in executive functions, memory, and metacognitive abilities, with associated impairment in emotional processes and social cognition. These deficits can compromise efforts in initiating and sustaining abstinence by hampering efficacy of clinical treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
220
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(234 citation statements)
references
References 155 publications
(249 reference statements)
10
220
0
4
Order By: Relevance
“…Additionally, and similar to other studies [33][34][35][36], participants were excluded if they: Self-reported as a daily smoker [37,38] Self-reported being pregnant [39] Exercised within 5 hours of testing [40] Consumed caffeine within 3 hours of testing [41] Had a concussion or head trauma within the past 30 days [42] Took marijuana or other illegal drugs within the past 30 days [43] Were considered a daily alcohol user (>30 drinks/month for women; >60 drinks/month for men) [44]…”
Section: Participantsmentioning
confidence: 99%
“…Additionally, and similar to other studies [33][34][35][36], participants were excluded if they: Self-reported as a daily smoker [37,38] Self-reported being pregnant [39] Exercised within 5 hours of testing [40] Consumed caffeine within 3 hours of testing [41] Had a concussion or head trauma within the past 30 days [42] Took marijuana or other illegal drugs within the past 30 days [43] Were considered a daily alcohol user (>30 drinks/month for women; >60 drinks/month for men) [44]…”
Section: Participantsmentioning
confidence: 99%
“…The backward condition of the VST taps both immediate visual memory and components of visuospatial working memory [149]. Therefore, lower scores in forward and backward span in AUD group indicate deficits in memory storage capacity as well as visual working memory, which are possibly resulting from chronic drinking in AUD individuals [11]. Interestingly, poor memory performance (low score on forward memory span) was associated with hyperconnectivity in three delta and alpha band connections, where AUD group showed both hyperconnectivity and poor memory performance.…”
Section: Poor Neuropsychological Performance In Audmentioning
confidence: 99%
“…These findings highlighted the intricate associations among neurocognitive performance, neural connectivity, and consistent impairments in AUD. While studies have shown that AUD individuals manifest impairments in multiple domains [63,64,[150][151][152][153] and some of these deficits can persist even after prolonged abstinence [11], it was surprising to find that AUD individuals did not manifest significant deficits in TOLT, which measures executive functioning such as planning and problem solving [68]. Interestingly, in our previous study with the same groups of subjects, we reported that that lower volumes in prefrontal cortex and left hippocampus observed in AUD group were associated with poorer visuospatial memory performance [16].…”
Section: Poor Neuropsychological Performance In Audmentioning
confidence: 99%
“…Neurocognitive effects of alcohol use have been well-studied and reviewed in depth elsewhere [40]. Briefly, alcohol use is associated with numerous cognitive deficits, which can hinder the impact of treatment efforts.…”
Section: Alcoholmentioning
confidence: 99%